Nutritional Intakes of Obese Elementary School Children Residing in the Shimokita Peninsula of Aomori, Japan - Takako Kumagai; Yumiko Nakamura; Emi Naijo; Akiko Sugimoto; Barry Kavanagh; Haruyuki Ito (International Journal of Public Health Science (IJPHS), 2014)
This research examined the lifestyles and eating habits of 42 elementary school fifth graders(20 boys and 22 girls) over a 3-day period; these children resided in theShimokita Peninsula, Aomori prefecture, which has the highest childhood obesityrate in Japan. The children’s nutritionalintakes were recorded via questionnaires and self-documented meal recorddiaries overa 3-day period (1 weekday and the weekend). The meal record diaries recorded which meals the children ate (including snacks) during the 3-day period. A regular feature of these children’s lifestyle was theviewing of at least 3 hours of television per day. Compared with the National Health and Nutrition Survey conductedby the Japanese government, the nutritionaland energy intake levels were the same but when we examined food group intakes,the vegetable intake was lower on weekends in comparison to the weekdays whenthe children were provided school lunches. In addition, salt intake exceededthe recommended standard in more than 80% of the study sample. We suggest thatthe pattern of reduced vegetable intake juxtaposed with high salt intake stemsfrom childhood and is repeated and passed down through generations; therefore, theguardians of these children require nutritional guidance and education.